A social history of the Irish music industry, 1910 - 1985 - Murphy, Michael Mary (Trinity College (Dublin, Ireland). Department of Sociology, 2015)
This thesis re-inserts a number of key behind-the-scenes individuals and factors into the history of the Irish music industry, placing the commercial and artistic achievements of Ireland's popular music artists in their industry context. By documenting a century of industry activity, it is possible to identify patterns of entrepreneurial activity, and ways in which the industry's development was shaped by internal and external factors.
Keywords: Social Sciences & Philosophy, Ph.D.; Ph.D. Trinity College Dublin.